Mind-Body Medicine in Children and Adolescents - Hilary McClafferty (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The primary goals of this Special Issue are to encourage readers to become more familiar with the range of mind-body therapies and to explore their application in the pediatric clinical setting. The Issue provides background and literature updates on several of the most commonly used mind-body therapies including biofeedback, clinical hypnosis, guided imagery, meditation, and yoga. The emerging technology of immersive virtual reality is also explored. The Special Issue includes a deliberate mix of case studies and practical clinical guidance, with the dual goals of piquing curiosity and providing resources for clinicians interested in pursuing further training.